Human Governance Development Index of Shariah Compliant Companies in Malaysia and Indonesia - Idris Gautama So; Hasnah Haron; Anderes Gui; Elfindah Princes; Synthia Atas Sari (WSEAS TRANSACTIONS on BUSINESS and ECONOMICS, 2024)
Volume 20